2017
DOI: 10.1016/j.foodchem.2016.10.115
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of Brazilian chia seeds grown in different places

Abstract: This study investigated and compared the occurrence and concentration of macronutrients, moisture, ash, dietary fiber, fatty acids, minerals, carotenoids, vitamins, flavonoids, phenolic compounds, antioxidant activity, phytate and tannin in Brazilian chia seeds grown in the states of Mato Grosso (MT) and Rio Grande do Sul (RS). High concentrations of lipids (31.2g.100g, on average), proteins (18.9g.100g, on average), dietary fiber (35.3g.100g, on average), vitamin E (8,203.6μg.100g, on average) were observed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
92
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(109 citation statements)
references
References 29 publications
14
92
1
2
Order By: Relevance
“…Tocopherols values obtained for chia oils in present study can be compared closely with the values reported for peanut oil (398.6 mg/kg), but lower than the values reported for flaxseed (588.5 mg/kg), sunflower (634.4 mg/kg), and soybean (1797.6 mg/kg) oils (Tuberosoet al, ). Chia seed oil contained 190.66 and 202.40 µg/100 g α‐tocopherol, 94.45 and 81.91 µg/100 g β‐tocopherol, and 7472.97 and 7487.69 µg/100 g ɣ‐tocopherols (da Silva et al, ). Tocopherol composition of raw chia seed oil showed significantly differences ( p < 0.05), and their tocopherol values were found higher than the roasted seed oil.…”
Section: Resultsmentioning
confidence: 99%
“…Tocopherols values obtained for chia oils in present study can be compared closely with the values reported for peanut oil (398.6 mg/kg), but lower than the values reported for flaxseed (588.5 mg/kg), sunflower (634.4 mg/kg), and soybean (1797.6 mg/kg) oils (Tuberosoet al, ). Chia seed oil contained 190.66 and 202.40 µg/100 g α‐tocopherol, 94.45 and 81.91 µg/100 g β‐tocopherol, and 7472.97 and 7487.69 µg/100 g ɣ‐tocopherols (da Silva et al, ). Tocopherol composition of raw chia seed oil showed significantly differences ( p < 0.05), and their tocopherol values were found higher than the roasted seed oil.…”
Section: Resultsmentioning
confidence: 99%
“…According to a study by Da Silva et al (2017), the amounts of phytic acid in chia seeds range between 0.96 and 1.16 g/100 g. EFSA (2018) noted the phytic acid content of white and whole wheat flour (about 0.4 g/100 g and 2.2 g/100 g, respectively), and of rye, rice, barley and oat flours (range: 0.45-0.75 g/ 100 g) as reported by Garcia-Estepa et al (1999). These authors also indicated that the From 3.5 lg/g in soy sprouts to 20 lg/g in soy seeds (Morandi et al, 2005) Genistin 3.4 UHPLC (Martinez-Cruz and Paredes-Lopez, 2014)…”
Section: Compositional Datamentioning
confidence: 99%
“…Chia seed ( Salvia hispanica L.) is a rich source of protein (18.9%), greater than in other traditional grains and therefore represents a promising source of bioactive peptides. Chia is an herbaceous plant native to Mexico and Central America, which supplies seeds that are noteworthy due their high nutritional and functional value .…”
Section: Introductionmentioning
confidence: 99%